2-echelon lastmile delivery with lockers and occasional couriers. (June 2022) - dos Santos, André Gustavo; Viana, Ana; Pedroso, João Pedro
Abstract: We propose a new approach for the lastmile delivery problem where, besides serving as collecting points of orders for customers, parcel lockers are also used as transshipment nodes in a 2-echelon delivery system. Moreover, we consider that a customer (occasional courier) visiting a locker may accept a compensation to make a delivery to another customer on their regular traveling path. The proposed shared use of the locker facilities – by customers that prefer to self-pick up their orders, and also as a transfer deposit for customers that prefer home delivery – will contribute to better usage of an already available storage capacity. Furthermore, the use of occasional couriers (OCs) brings an extra layer of flexibility to the delivery process and may positively contribute to achieving some environmental goals: although non-consolidation of deliveries may, at first sight, seem negative, by only considering OCs that would go to the locker independently of making or not a delivery on their way home, and their selection being constrained by a maximum detour, the carbon footprint can be potentially reduced when compared to that of dedicated vehicles. We present a mixed-integer linear programming formulation for the problem that integrates three delivery options – depot to locker, depot to locker followed by final delivery by a professional fleet, and depot to locker followed by final delivery by an OC. Furthermore, to assess the impact of OCs' no show on the delivery process, we extend the formulation to re-schedule the delivery of previous undelivered parcels, and analyze the impact of different no-show rates. Thorough computational experiments show that the use of OCs has a positive impact both on the delivery cost and on the total distance traveled by the dedicated fleets. Experiments also show that the negative impact of no-shows may be reduced by using lockers with higher capacities. Highlights: A novel 2-echelon VRP Integer Programming model for lastmile delivery. Combined use of a professional fleet and occasional couriers (OCs). Parcel lockers that act as collecting and as intermediate delivery points. OCs pick their own order(s) from a locker, but can also deliver to other clients. A new multi-period model re-schedules undelivered parcels due to OCs no-shows.